2020
DOI: 10.1177/1040638720927669
|View full text |Cite
|
Sign up to set email alerts
|

Cases of high mortality in cull sows and feeder pigs associated with Streptococcus equi subsp. zooepidemicus septicemia

Abstract: Investigations of 2 cases of high mortality in cull sows and feeder pigs from a buying station in Ohio and cull sows at an abattoir in Tennessee were conducted at the Iowa State University Veterinary Diagnostic Laboratory. The animals were presented as weak, lethargic, and some with high fever. Rapidly escalating mortality was reported to be as high as 30–50% within groups at the buying station over 8–10 d, and 30–40% over 5–7 d at the abattoir. Splenomegaly and red lymph nodes were the most consistent macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Pigs rapidly develop depression, anorexia, and high fever. Field mortality rates reach 30–50% ( 6 ). Experimental replication of disease revealed the susceptibility of healthy, conventionally raised pigs to SEZ which results in 100% mortality within 72 h of challenge ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pigs rapidly develop depression, anorexia, and high fever. Field mortality rates reach 30–50% ( 6 ). Experimental replication of disease revealed the susceptibility of healthy, conventionally raised pigs to SEZ which results in 100% mortality within 72 h of challenge ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been infrequently associated with disease in pigs in North America (3); however, in 2019, SEZ was isolated from swine that died during high mortality events in the USA and Canada (4)(5)(6). Pigs developed weakness, lethargy, high fever, and mortality rates of 30-50% over 5-10 days following infection (6). Initial investigation into the pathogenesis of mortality event isolates revealed that SEZ is capable of causing disease in healthy, conventionally raised pigs and experimental exposure resulted in 100% mortality within 72 h post-challenge (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcus equi subsp. zooepidemicus ( S. zooepidemicus ), is a β-hemolytic streptococcus belonging to the Lancefield group C. It is a rare human pathogen, but it is commonly isolated from bacterial infections in a wide range of animal species like horses [ 1 ], dogs [ 2 , 3 ], felines [ 4 , 5 , 6 ], swine [ 7 , 8 ], guinea pigs [ 9 ], ruminants [ 10 , 11 ], camelids [ 12 ] and non-human primates [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…zooepidemicus . 10 The ability to internally validate Dx code alignment is possible. For example, respiratory and digestive systems represented 61.4% of the overall Dx code assignments; body system can be automatically implied or can have additional validation by confirming the presence of compatible lesion codes such as bronchopneumonia or enteritis, both of which are encountered commonly.…”
Section: Discussionmentioning
confidence: 99%